2012
DOI: 10.1021/ja303696s
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Orientation of the Peptide-Bridge Dipole Moment on the Properties of Fullerene–Peptide–Radical Systems

Abstract: We synthesized two series of compounds in which a nitroxide radical and a fullerene C 60 moiety were kept separated by a 3 10 -helical peptide bridge containing two intramolecular CO···H−N hydrogen bonds. The direction of the resulting molecular dipole moment could be reversed by switching the position of fullerene and nitroxide with respect to the peptide nitrogen and carbon termini. The resulting fullerene−peptide−radical systems were compared to the behaviors of otherwise identical peptides but lacking eit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
36
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 79 publications
4
36
0
Order By: Relevance
“…For example, different ET (or electron‐transport) rates have been found for opposite orientations of the peptides in SAMs; similar effects were observed for ET in freely diffusing donor–peptide–acceptor systems . Thermodynamics, however, could also be responsible for making ET rates different: as a matter of fact, we already showed that an oriented peptide dipole moment affects significantly the redox potentials of electroactive groups and gold clusters . For molecules in solution, as opposed to the concept of dyads, in which two moieties are separated by a spacer, we concluded that moieties separated by Aib peptides must be described also by stressing the orientation of the bridge, because its dipole moment is capable of tuning the system's physicochemical properties (not just electrochemistry) significantly .…”
Section: Resultsmentioning
confidence: 53%
See 1 more Smart Citation
“…For example, different ET (or electron‐transport) rates have been found for opposite orientations of the peptides in SAMs; similar effects were observed for ET in freely diffusing donor–peptide–acceptor systems . Thermodynamics, however, could also be responsible for making ET rates different: as a matter of fact, we already showed that an oriented peptide dipole moment affects significantly the redox potentials of electroactive groups and gold clusters . For molecules in solution, as opposed to the concept of dyads, in which two moieties are separated by a spacer, we concluded that moieties separated by Aib peptides must be described also by stressing the orientation of the bridge, because its dipole moment is capable of tuning the system's physicochemical properties (not just electrochemistry) significantly .…”
Section: Resultsmentioning
confidence: 53%
“…Thermodynamics, however, could also be responsible for making ET rates different: as a matter of fact, we already showed that an oriented peptide dipole moment affects significantly the redox potentials of electroactive groups and gold clusters . For molecules in solution, as opposed to the concept of dyads, in which two moieties are separated by a spacer, we concluded that moieties separated by Aib peptides must be described also by stressing the orientation of the bridge, because its dipole moment is capable of tuning the system's physicochemical properties (not just electrochemistry) significantly . A final mention is about the important effect of oriented dipole moments on the metal work function and associated applications.…”
Section: Resultsmentioning
confidence: 93%
“…[28][29][30][31] In synthetic polypeptide helices, the intrinsic dipoles rectify the directionality of CT. [32][33][34][35][36][37] The broadband gap [or highest occupied molecular orbital (HOMO)-lowest unoccupied molecular orbital (LUMO) gap] of proteins, however, along with the inability to inject charges in them without chemically cleaving their backbones, [38][39][40] considerably limits their utility as electronic materials. Proteins and polypeptides (composed of native α-amino acids and their derivatives) mediate ET solely via tunneling, the efficiency of which is limited to about 2 nm.…”
Section: Ct Molecular Electrets: Practical Ideas From Structural Biologymentioning
confidence: 99%
“…When the structures with opposing dipole direction are not completely symmetrical, the differences in the electronic coupling can prevail over the dipole-induced effect for relatively large −ΔG CT (0) [125]. Since the beginning of the 21 st century, studies of dipole effects on CT have focused on systems comprising polypeptide helices [12,95,99,[126][127][128][129][130][131][132][133][134][135][136][137][138][139][140][141]. Donor-bridge-acceptor (DBA) constructs, where the bridge is a helix, allow for testing dipole-induced charge-transfer rectification, i.e.…”
Section: Dipole Effects On Charge Transfermentioning
confidence: 99%
“…the difference between the rates of ET along the dipole vs. ET against the dipole [137]. Self-assembled monolayers (SAMs) of polypeptide helices on gold surfaces show similar dipole-induced rectification of interfacial CT [95], i.e.…”
Section: Dipole Effects On Charge Transfermentioning
confidence: 99%